2010
DOI: 10.1021/ma100047z
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fickian Diffusion of Water in Nafion

Abstract: Understanding the dynamics of water in solid-state polymer electrolytes (e.g., Nafion) is important for a variety of applications ranging from membrane-based water purification to hydrogen fuel cells. In this study, the dynamics of water in Nafion was investigated at both low and high humidities with time-resolved Fourier transform infrared-attenuated total reflectance (FTIR-ATR) spectroscopy; a technique that provides a molecular fingerprint of both the diffusant and the polymer simultaneously in real time. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(169 citation statements)
references
References 62 publications
11
157
1
Order By: Relevance
“…The MIR region has been already highly documented in Nafion and other PFSA membranes, 10,[16][17][18][19][20][21][22]43 but the FIR spectra were never reported in the literature. 3D plots of a typical hydration sequence from dry to 100%RH are shown in Figure 1 The 3D plots evidence several distinct mechanisms identified through the appearance or disappearance of characteristic bands in both the FIR and MIR.…”
Section: Resultsmentioning
confidence: 99%
“…The MIR region has been already highly documented in Nafion and other PFSA membranes, 10,[16][17][18][19][20][21][22]43 but the FIR spectra were never reported in the literature. 3D plots of a typical hydration sequence from dry to 100%RH are shown in Figure 1 The 3D plots evidence several distinct mechanisms identified through the appearance or disappearance of characteristic bands in both the FIR and MIR.…”
Section: Resultsmentioning
confidence: 99%
“…14, 19, 21, 26, 30, 31 Our earlier studies have shown that 40 wt% [C 2 mim][TfO] uptake is above the critical IL uptake where the conductivity of the ionomer/IL membrane exhibits much higher conductivity (~ 9 × 10 −6 S/cm) than that of the pure ionomer. 14, 32, 33 It should also be noted that the Aquivion membrane without ILs exhibits very low ionic conductivity which makes it unsuitable for studying the charge dynamics here.…”
Section: Methodsmentioning
confidence: 99%
“…34,36 Yet, as recently highlighted by Hallinan et al, most of the results were obtained using experimental cells subjected to a low flow of humidified gas, which does not provide a constant water concentration at the membrane surface, as required to properly use Fick's model. 36,37 Consequently, in these studies the water uptake should be controlled by the interfacial transport resistance, biasing the D m measurements, as first evidenced by Satterfield and Benziger. 35 The influence of interfacial effects can be overcome by forcing a constant boundary condition during the sorption process, i.e., by contacting the membrane with liquid water.…”
Section: ■ Introductionmentioning
confidence: 92%